2020
DOI: 10.3390/ijerph17051641
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Crisis Line Volunteering on Mental Wellbeing and the Associated Factors: A Systematic Review

Abstract: Crisis line services, operated by volunteers, have been proven to be effective in decreasing psychological pain and preventing suicidality. Although working at the crisis line may be rewarding, for some the confrontation with highly complex topics (i.e., suicidality, abuse, and loneliness) in combination with inappropriate calls (i.e., sexually abusive calls), may lead to distress or vicarious trauma. The aim of this paper is to systematically review the studies that have examined mental wellbeing of crisis li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(66 citation statements)
references
References 55 publications
5
57
1
3
Order By: Relevance
“…Even though BOS has been extensively characterized in emergency healthcare personnel 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ) , research on FAVs is relatively scarce, and evidence is somewhat conflicting, particularly for Italian personnel. For instance, a study on a small sample of Italian Red Cross volunteers did not list BOS as a major problem 42 ) , and two Italian studies, including a little group of ambulance driver-rescuers, reported inconsistent findings 43 , 44 ) .…”
Section: Introductionmentioning
confidence: 99%
“…Even though BOS has been extensively characterized in emergency healthcare personnel 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ) , research on FAVs is relatively scarce, and evidence is somewhat conflicting, particularly for Italian personnel. For instance, a study on a small sample of Italian Red Cross volunteers did not list BOS as a major problem 42 ) , and two Italian studies, including a little group of ambulance driver-rescuers, reported inconsistent findings 43 , 44 ) .…”
Section: Introductionmentioning
confidence: 99%
“…They indicated that there were many areas in the field of suicidology which they should learn. Unfortunately, there are no international studies where this issue is addressed, albeit a research team under R. Willems has indeed concluded that volunteers need training and coaching on how to talk to difficult callers (Willems et al, 2020). There are, however, papers on specific training offered to helpline workers and volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…Roche and J. Ogden (2017). In yet another study, many volunteers showed symptoms of burnout, stress, frustration, and irritation, which may have been caused by their insufficient experience in communicating with people in need of support (Willems et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…On peut ainsi se demander si la mise en place de ces hotlines n'a pas ré pondu aux besoins des responsables politiques et des intervenants plus qu'à ceux de la population. À cet é gard, la litté rature sur les hotlines laisse voir la forte motivation des personnes engagé es [2] et les possibles effets bé né fiques d'un tel engagement [15], mais les donné es sur les appelants et les bé né fices pour eux sont plus rares [10]. L'intuition clinique de l'utilité du soutien psychologique par té lé phone existe dans de nombreux domaines, mais la litté rature empirique à ce propos est quasiment inexistante, et les bé né fices directs pour les usagers sont difficiles à dé montrer [10].…”
Section: Les Hotlines De Soutien Psychologiqueunclassified